Corn (Zea mays L.) response to sublethal rates of paraquat and fomesafen at vegetative growth stages. (August 2019) - Sperry, Benjamin P.; Lawrence, Benjamin H.; Bond, Jason A.; Reynolds, Daniel B.; Golden, Bobby R.; Edwards, Henry M.
Abstract: Research was conducted from 2013 to 2015 across three sites in Mississippi to evaluate corn response to sublethal paraquat or fomesafen (105 and 35 g ai ha −1, respectively) applied PRE, or to corn at the V1, V3, V5, V7, or V9 growth stages. Fomesafen injury to corn at three d after treatment (DAT) ranged from 0% to 38%, and declined over time. Compared with the nontreated control (NTC), corn height 14 DAT was reduced approximately 15% due to fomesafen exposure at V5 or V7. Exposure at V1 or V7 resulted in 1, 220 and 1, 110 kg ha −1 yield losses, respectively, compared with the NTC, but yield losses were not observed at any other growth stage. Fomesafen exposure at any growth stage did not affect corn ear length or number of kernel rows relative to the NTC. Paraquat injury to corn ranged from 26% to 65%, depending on growth stage and evaluation interval. Corn exposure to paraquat at V3 or V5 consistently caused greater injury across evaluation intervals, compared with other growth stages. POST timings of paraquat exposure resulted in corn height reductions of 13% to 50%, except at V7, which was most likely due to rapid internode elongation at that stage. Likewise, yield loss occurred after all exposure times of paraquat except PRE, compared with the NTC. Corn yield was reduced 1, 740 to 5, 120 kg ha −1 compared with the NTC, generally worsening as exposure time was delayed. Paraquat exposure did not reduce corn ear length, compared with the NTC, at any growth stage. However, paraquat exposure at V3 or V5 was associated with reduction of kernel rows by 1.1 and 1.7, respectively, relative to the NTC. Paraquat and fomesafen applications near corn should be avoided if conditions are conducive for off-target movement, because significant injury and yield loss can result.